KEKELIRUAN PRAANGGAPAN DALAM MENCIPTAKAN HUMOR PADA FILM “JATUH CINTA SEPERTI DI FILM-FILM” - Mukodas Mukodas; Miranti Miranti (Universitas Batanghari, 2025)
This study examines humor construction in Jatuh Cinta Seperti di Film-Film from a pragmatic perspective, focusing on the fallacy of presumption. It aims to describe how humor arises from differences in assumptions between characters in dialogues and interactions. The subject is Falling in Love Like in the Movies, an award-winning romantic comedy. Using a descriptive qualitative approach, this study finds that the fallacy of presumption plays a crucial role in creating subtle yet effective humor without relying on slapstick or verbal insults. Misunderstandings between characters generate sharp, context-driven comedy. The study further demonstrates that humor can emerge from exploring meaning and irony in conversation rather than merely visual or situational elements. By contributing to pragmatic linguistics, this research introduces a new perspective on ethical and intellectual humor in film. It also proves that humor based on presumption fallacies can be both entertaining and educational, offering a more respectful and relevant model for society.